إدارة المواهب في المؤسسة الاقتصادية الجزائرية: الواقع والأفاق دراسة حالة Enmtp / Umd – قسنطينة- - قريشي, محمد الصالح; هواري, حنان; بوشريبة, محمد (University of Eloued جامعة الوادي, 2019)
هدفت الدراسة إلى إسقاط مقاربة إدارة المواهب على المؤسسة الاقتصادية الجزائرية من خلال تقييم مستوى تطبيق استراتيجيات إدارة المواهب في فرع UMDالتابع للمؤسسة الاقتصاديةENMTP - قسنطينة. ومن أجل بلوغ هدف الدراسة عمد الباحثين على وضع إطار منهجي ارتكز من جهة على المنهج الوصفي بأساليبه التحليلي ودراسة الحالة والإحصائي، ومن جهة أخرى على الاستبيان كأداة رئيسية لجمع البيانات، هذا إلى جانب عينة للدراسة بلغ حجمها 111 مفردة. وتوصلت الدراسة إلى أن مستوى تطبيق إستراتيجيات إدارة المواهب على مستوى وحدة UMD لا يرقى إلى المستوى المطلوب Abstract: The study aimed to examine the talent management approach on the Algerian economic organizations by evaluating the level of talent management strategies in UMD affiliated to the Economic Corporation ENMTP -Constantine. In order to achieve the purpose of this study, the researchers had used a methodological framework based on the descriptive research in its tools; analysis, case study and statistical method, and in the other side applied a questionnaire, which was developed to collect data as the main tool. When the sample of the study consisted of 111 employees. The study found that the level of practicing Talent Management Strategies at UMD. is not up to the required level
Talent management In the Algerian Economic Enterprise: Reality and prospects Case study of UMD /ENMTP Constantine
مقال - مجلة رؤى اقتصادية
Keywords: مواهب ; إدارة المواهب ; استراتيجيات؛ الترميز الاقتصادي ) JEL :) M12; talents, talent management, strategies. Jel Classification Codes: M12